2011
DOI: 10.1371/annotation/f585335f-ff77-40ae-a8b6-ad6019af31aa
|View full text |Cite
|
Sign up to set email alerts
|

Correction: In-Depth Analysis of the Antibody Response of Individuals Exposed to Primary Dengue Virus Infection

Abstract: Humans who experience a primary dengue virus (DENV) infection develop antibodies that preferentially neutralize the homologous serotype responsible for infection. Affected individuals also generate cross-reactive antibodies against heterologous DENV serotypes, which are non-neutralizing. Dengue cross-reactive, non-neutralizing antibodies can enhance infection of Fc receptor bearing cells and, potentially, exacerbate disease. The actual binding sites of human antibody on the DENV particle are not well defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This study also confirms that indirect anti-NS1 ELISA has poor diagnostic performance (AUC 0.56, 95% CI 0.43-0.69) in detecting IgM antibodies in acute-phase to early convalescent-phase DENV infected sera (Figure S1A). This finding could be due to the relatively high abundance of anti-prM/E antibodies in DENV infected individuals, as reported in previous studies [14,47,48]. Additionally, the reduced sensitivity of indirect NS1 IgM ELISA could be due to the competition between two antibody isotypes, i.e., IgM and IgG, for the same antigenic sites.…”
Section: Discussionmentioning
confidence: 53%
“…This study also confirms that indirect anti-NS1 ELISA has poor diagnostic performance (AUC 0.56, 95% CI 0.43-0.69) in detecting IgM antibodies in acute-phase to early convalescent-phase DENV infected sera (Figure S1A). This finding could be due to the relatively high abundance of anti-prM/E antibodies in DENV infected individuals, as reported in previous studies [14,47,48]. Additionally, the reduced sensitivity of indirect NS1 IgM ELISA could be due to the competition between two antibody isotypes, i.e., IgM and IgG, for the same antigenic sites.…”
Section: Discussionmentioning
confidence: 53%
“…A study that analyzed antibodies produced in human postprimary DENV infection found low amounts of highly specific and neutralizing antibodies that were mainly against the envelope EDIII domain. On the other hand, they found that most weakly cross-reactive antibodies were against prM (71). Preexisting neutralizing antibodies can prevent DENV attachment to its natural receptor on the cell surface thus inhibiting virus entry (Figure 4B).…”
Section: Challenges Face Dengue Vaccine Development Antibody Dependent Enhancement (Ade)mentioning
confidence: 99%
“…During primary infection, the activation of DENV-specific naïve B cells gives rise to both antibody-secreting long-lived plasma cells (LLPCs), which reside primarily in the bone marrow, and memory B cells (MBCs), which circulate through the blood and secondary lymphoid organs. Extensive analyses of monoclonal antibodies (mAbs) and polyclonal sera of individuals with history of a primary DENV infection revealed that the majority of antibodies is cross-reactive and weakly neutralising, and that only a minor proportion of antibodies is responsible for durable, strong serotype-specific neutralisation [104][105][106][107][108][109][110][111][112][113][114][115]. Transient immunity to heterologous serotypes observed after primary infection is thought to depend on the concentration of cross-reactive antibodies in serum.…”
Section: The Neutralising Antibody Response To Denv Infectionmentioning
confidence: 99%
“…Several screening studies observed immunodominance of the EDI/II region in DENV-immune donors and found that it was mainly targeted by cross-reactive antibodies displaying weak neutralising activity [104][105][106]110,121,[142][143][144][145]. The majority of these antibodies have been mapped to a region comprising the FL in EDII (amino acids 98 to 110), termed the fusion loop epitope (FLE) [71,104,105,110,123,142,144,146].…”
Section: Antibodies That Target the Fusion Loop Epitope In The E Proteinmentioning
confidence: 99%